2016
DOI: 10.1007/s13762-016-0960-0
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption kinetics and thermodynamics of organophosphorus profenofos pesticide onto Fe/Ni bimetallic nanoparticles

Abstract: Bimetallic Fe/Ni nanoparticles were synthesized and used for the removal of profenofos organophosphorus pesticide from aqueous solution. These novel bimetallic nanoparticles (Fe/Ni) were characterized by scanning electron microscopy, energy-dispersive X-ray analysis spectroscopy, X-ray diffraction, and Fourier transform infrared spectroscopy. The effect of the parameters of initial pesticide concentration, pH of the solution, adsorbent dosage, temperature, and contact time on adsorption was investigated. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 63 publications
0
12
0
2
Order By: Relevance
“…In the diffraction pattern of the catalysts, no characteristic diffraction peak of Ni was observed, proving that Ni was highly dispersed on the surface of montmorillonite and may be close to amorphous or single-layer distribution. The above results showed that the addition of Ni could effectively promote the miniaturization of Fe grains and prevent the agglomeration of Fe 47 . The surface morphology of the different montmorillonite composites was shown in Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In the diffraction pattern of the catalysts, no characteristic diffraction peak of Ni was observed, proving that Ni was highly dispersed on the surface of montmorillonite and may be close to amorphous or single-layer distribution. The above results showed that the addition of Ni could effectively promote the miniaturization of Fe grains and prevent the agglomeration of Fe 47 . The surface morphology of the different montmorillonite composites was shown in Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Results obviously demonstrated that the bimetals were homogeneously distributed in the Fe/Ni montmorillonite material, and montmorillonite could effectively inhibit the agglomeration of Fe/Ni particles. Uniformly distribution of Ni and Fe made active sites exposed, which facilitated the contact of target contaminants with active sites and improved the degradation of the catalyst 47 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Estos experimentos son los más comunes para el estudio de adsorción ya sea de compuestos orgánicos, como inorgánicos o metales [67][68][69].…”
Section: -Experimentos De Adsorción En Discontinuounclassified
“…Due to its high efficiency and easy operation, adsorption is one of the most important methods for removal of organic pollutants [5,6]. Adsorbents used in pesticide remediation from water and wastewater have been already developed [7,8]. Among the popularly used sorbents, activated carbon is the most employed one for removal of pollutants from wastewaters.…”
Section: Introductionmentioning
confidence: 99%